Penelitian Registrasi Kanker Population Based di daerah Istimewa Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
ABSTRAK The relative frequency and incidence of cancer in the area of Yogyakarta have been reported on the basis of pathology departments or usually hospital-based registries. Population-based rates, for which a good cancer registry is needed, have not yet been tried. A preliminary study for the establishment of a population registry was carried out in the area of Yogyakarta. This preliminary study area was divided into two parts, one located in the Bantul district and in the city of Yogyakarta for hospital-based studies, and one in the Srandakan sub-district for population-based studies. In the Srandakan sub-district, Bantul district intensive home visits were made, while a motivation programme for medical and non-medical institutions will undertaken in Bantul district (excluding Srandakan district) and the city of Yogyakarta. The results indicated that cancer incidence rates in the Srandakan sub-district were two to four times higher than in the Bantul district and the city of Yogyakarta., suggesting that cancer rates derived from population-based data are higher than those from hospital-based data. Therefore the population based cancer registry should be developed in Yogyakarta.